New inhibitors for dicarbonyl/L-xylulose reductase in Caenorhabditis elegans - Tho Son, Le; Hai Dang, Nguyen; Thi Phuong, Lai; Thi Thu, Nguyen; Huy Hoang, Nguyen (Vietnam Journal of Biotechnology, 2022)
Dicarbonyl/L-xylulose reductase (DCXR) is an enzyme reducing dicarbonyl (-CO-) groups in single sugar molecules and participates in the sugar metabolism of several sugar metabolism cycles in different living organisms (humans, other animals, fungi, and microorganisms). Caenorhabditis elegans, a model organism, has a unique DCXR (referred to as Ce DCXR) which plays a biochemical function similar to its homologs in the other organisms. However, the catalytic regulation of the enzyme has not been fully elucidated yet. Therefore, in this study, we investigated the chemicals which could inhibit the enzyme and found three inhibitor compounds including hexanoic acid, phosphoenolpyruvic acid, and DL-α-aminobutyrate hydrochloride for the enzyme. Because these inhibitors and their derivatives suppressed DCXRs in humans, mice, rabbits, and rats, they possibly inhibit the DCXR homologs at least in other animals. If the inhibitors and their derivatives are components in pharmaceutical products, foods, and drinks, they may come into cells, interact with DCXRs and inactivate them, causing toxicity for the host organisms.